2022
DOI: 10.3390/nano12050749
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Albumin Pre-Coating on Gold Nanoparticles Uptake at Single-Cell Level

Abstract: Nanoparticles (NPs) suspension is thermodynamically unstable, agglomeration and sedimentation may occur after introducing NPs into a physiological solution, which in turn affects their recognition and uptake by cells. In this work, rod-like gold NPs (AuNRs) with uniform morphology and size were synthesized to study the impact of bovine serum albumin (BSA) pre-coating on the cellular uptake of AuNRs. A comparison study using horizontal and vertical cell culture configurations was performed to reveal the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Although the latter method yielded similar average AuNP uptake by cells (Figure S8), it failed to reveal the heterogeneity of AuNP uptake across cell populations. Cellular NP uptake could alternatively be determined by single-cell ICP-MS (SC-ICP-MS), in which individual cells carried by nebulized aerosols are sent into ICP torch for ionization followed by MS analysis. , Without the axial dispersion in the gas path before the ICP torch, an individual cell will generate a sharp signal peak in SC-ICP-MS with a width below 1 ms, increasing the risk of detector saturation. Furthermore, absolution quantification by SC-ICP-MS is also limited by the lack of matrix-matched particulate standards, making it impossible to verify whether hundreds of NPs internalized by one cell could generate a mass-signal response equivalent to that of a single NP.…”
Section: Resultsmentioning
confidence: 99%
“…Although the latter method yielded similar average AuNP uptake by cells (Figure S8), it failed to reveal the heterogeneity of AuNP uptake across cell populations. Cellular NP uptake could alternatively be determined by single-cell ICP-MS (SC-ICP-MS), in which individual cells carried by nebulized aerosols are sent into ICP torch for ionization followed by MS analysis. , Without the axial dispersion in the gas path before the ICP torch, an individual cell will generate a sharp signal peak in SC-ICP-MS with a width below 1 ms, increasing the risk of detector saturation. Furthermore, absolution quantification by SC-ICP-MS is also limited by the lack of matrix-matched particulate standards, making it impossible to verify whether hundreds of NPs internalized by one cell could generate a mass-signal response equivalent to that of a single NP.…”
Section: Resultsmentioning
confidence: 99%
“…The results, shown in Figure S2, indicate no observable effects from the albumin coronas in the uptake of the SPIONs in the breast cancer cells. These results are consistent with prior studies where albumin is reported to affect cellular uptake in negative ways as it has the property of reducing the interaction of the NPs with the surroundings such as other proteins or cell membranes. , Although not affecting directly, it is possible that albumin acts by reducing the non-specific interaction of the NPs with the cells, thereby allowing the Rf ligand to promote the interaction with the cells and resulting in the enhanced uptake of the Rf-SPIONs.…”
Section: Discussionmentioning
confidence: 99%
“…119,121 Exploring the appropriate size of AuNPs that can cross the BBB to exert anti-neuroinflammatory effects while avoiding causing cytotoxicity is a worthwhile direction to explore (Table 2). 122–124…”
Section: Clinical Applicationsmentioning
confidence: 99%